Understanding the Hadith of the Prophet from Gender Perspective (Female Leadership, Lack of Reason, Aurat Female Voice) According to Muhammad Al Ghazali - Nisa A-Zahro Jauzaa’; Syamsul Bakri (al-Afkar, Journal For Islamic Studies, 2024)
Justice has always been a reason to interpret gender issues as inequality in people's lives. So a gender-oriented interpretation is needed. Hadith is the main source of Islamic teachings, occupying a position as details and explanations of the Quran. The hadiths about gender in this discussion include hadiths about women's leadership, women lack reason, women's voices are aurat. The method used in this research is the library method. In recent times, contemporary scholars have tried to understand hadith, Al Ghazali is one of the contemporary figures who offers a method of understanding hadith between textual and contextual understanding. According to him, the method of understanding the hadith of the Prophet Muhammad SAW. must be measured from four criteria for the validity of the hadith matan; 1) Matan Hadith must be in accordance with the Koran, 2) Conformity of Hadith with other authentic Hadith, 3) Conformity with Historical Facts 4) Conformity with Scientific Truth. Even though it is considered controversial, it must be admitted that the method he proposed has made a significant contribution to answering various problems of the people today. His thinking in upholding women's rights also needs to be appreciated.